2017
DOI: 10.1007/s13592-017-0549-8
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of RNA viruses in Tasmanian-introduced bumble bees (Bombus terrestris) and honey bees (Apis mellifera)

Abstract: A number of bee RNA viruses, including Deformed wing virus (DWV), are so far unreported from Australia. These viruses can be introduced together with imported live honey bees (Apis mellifera) and their products, with other bee species, and bee parasites. Given that bee viruses have a profound impact on bee health, it is surprising that since the introduction of bumble bees (Bombus terrestris) onto Tasmania in 1992 from New Zealand, no work has been done to investigate which RNA viruses are associated with thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…This may be related to the haplodiploid sex determination system of bees, that results in increased purging of deleterious recessive alleles expressed in haploid males ( Schmid-Hempel et al 2007 ). Tasmanian B. terrestris may also further benefit from a reduced load of pathogenic viruses ( Allen et al 2007 ), although two viruses, the Kashmir bee virus (KBV) and Sacbrood virus (SBV) are now prevalent in the south-eastern Tasmanian populations ( Fung et al 2018 ).…”
mentioning
confidence: 99%
“…This may be related to the haplodiploid sex determination system of bees, that results in increased purging of deleterious recessive alleles expressed in haploid males ( Schmid-Hempel et al 2007 ). Tasmanian B. terrestris may also further benefit from a reduced load of pathogenic viruses ( Allen et al 2007 ), although two viruses, the Kashmir bee virus (KBV) and Sacbrood virus (SBV) are now prevalent in the south-eastern Tasmanian populations ( Fung et al 2018 ).…”
mentioning
confidence: 99%
“…Interestingly, contrary to our findings in New Zealand the incipient bumble bee populations in Tasmania were apparently free from pathogens including C. bombi and N. bombi, and displayed no wing deformities that might be associated with DWV (Allen et al 2007). More recent work on the Tasmanian B. terrestris has also failed to find DWV, but has found these bumble bees to be infected with both the Kashmir bee virus and Sacbrood virus (Fung et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, once bumblebees become infected, they could potentially then go on to become sources for new spillover events. Fung et al (2018) investigated whether the introduction of bumblebees (B. terrestris) into the (Varroa-free) island of Tasmania had resulted in the co-introduction of known honey bee viruses. Whilst it was shown that Kashmir bee virus (KBV) and Sacbrood virus (SBV) were present in both honey bees and B. terrestris and were probably shared between these species, it was not possible to determine whether the viruses were introduced along with bumblebees or had previously been introduced with honey bees, as the same viruses were also found in honey bees on the Australian mainland (the souce of the Tasmanian honey bee population).…”
Section: Bumblebeesmentioning
confidence: 99%